Glycosylation of ceramide synthase 6 is required for its activity - Alexandra J. Straus; Grace Mavodza; Can E. Senkal (Journal of Lipid Research)
Sphingolipids play key roles in membrane structure and cellular signaling. Ceramide synthase (CerS)-generated ceramide is implicated in cellular stress responses and induction of apoptosis. Ceramide and other sphingolipids are linked to the induction of ER stress response pathways. However, the mechanisms by which ceramide modulates ER stress signaling are not well understood. Here, we show that the ER stress inducer brefeldin A (BFA) causes increased glycosylation of CerS6, and that treatment with BFA causes increased endogenous ceramide accumulation. To our surprise, we found that CerS6 activity was not affected by BFA-induced glycosylation. Instead, our data show that basal glycosylation of CerS6 at Asn18 is required for CerS6 activity. We used a robust HCT116 CRISPR-Cas9 CerS6 KO with reintroduction of either WT CerS6 or a mutant CerS6 with a point mutation at asparagine-18 to an alanine (N18A) which abrogated glycosylation at that residue. Our data show that cells stably expressing the N18A mutant CerS6 had significantly lower activity in vitro and in situ as compared to WT CerS6 expressing cells. Further, the defective CerS6 with N18A mutation also had defects in GSK3β, AKT, JNK, and STAT3 signaling. Despite being required for CerS6 activity, Asn18 glycosylation did not influence ER stress response pathways. Overall, our study provides vital insight into the regulation of CerS6 activity by posttranslational modification at Asn18 and identifies glycosylation of CerS6 to be important for ceramide generation and regulation of downstream cellular signaling pathways.